2013
DOI: 10.1016/j.neuroscience.2013.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of brain nuclei accessible to ghrelin present in the cerebrospinal fluid

Abstract: Ghrelin is a stomach-derived peptide hormone that acts in the brain to regulate many important physiological functions. Ghrelin receptor, named the growth hormone secretagogue receptor (GHSR), is present in many brain areas with or without obvious direct access to ghrelin circulating in the bloodstream. Ghrelin is also present in the cerebrospinal fluid (CSF) but the brain targets of CSF ghrelin are unclear. Here, we studied which brain areas are accessible to ghrelin present in the CSF. For this purpose, we c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
93
0
16

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(119 citation statements)
references
References 49 publications
10
93
0
16
Order By: Relevance
“…Interestingly, in the present study intra-VTA ghrelin robustly increased food intake in mice on both a chow and HFD suggesting HFD per sedoes not cause ghrelin resistance directly in the VTA. However, intra-VTA injection represents a non-physiological source of exogenous ghrelin into the VTA and studies show that peripheral ghrelin access into the brain is largely limited to the hypothalamus (Cabral et al, 2013;Cabral et al, 2014). When we performed linear regression analysis we observed a clear correlation between intra-VTA ghrelin-induced feeding and body weight in chow, but not HFD mice.…”
Section: Discussionmentioning
confidence: 73%
“…Interestingly, in the present study intra-VTA ghrelin robustly increased food intake in mice on both a chow and HFD suggesting HFD per sedoes not cause ghrelin resistance directly in the VTA. However, intra-VTA injection represents a non-physiological source of exogenous ghrelin into the VTA and studies show that peripheral ghrelin access into the brain is largely limited to the hypothalamus (Cabral et al, 2013;Cabral et al, 2014). When we performed linear regression analysis we observed a clear correlation between intra-VTA ghrelin-induced feeding and body weight in chow, but not HFD mice.…”
Section: Discussionmentioning
confidence: 73%
“…Moreover, a recent study by Bonn et al, demonstrates that the 5-HT2C receptor can also be found on NPY producing neurons 75,76 , which was previously not recognized. In addition, a significant number of neurons in the hippocampus express the GHS-R1a receptor 51,58,[77][78][79] as well as do most regions of the hypothalamus [50][51][52] . Specifically, in the arcuate nucleus, the GHS-R1a receptor is strongly expressed on NPY neurons, with 94% of the NPY neurons demonstrating GHS-R1a mRNA, but also on the POMC neurons , albeit only in 8% of the POMC neurons 80 .…”
Section: Co-localization Of the 5-ht2c Receptor And Fluorescein-ghrelmentioning
confidence: 99%
“…Therefore, neurons were cultured from rat pups at E17 to ensure 5-HT2C receptor expression. Central expression of the GHS-R1a receptor was analysed using a variation of a recently described method using fluorescein-ghrelin 82 , a novel strategy to detect specific GHS-R1a receptor expression 58 Figure 5A). This is in line with previous findings from our lab and others demonstrating that a single administration of ghrelin causes an acute increase in food intake which is diminished over time 4,83 .…”
Section: Co-localization Of the 5-ht2c Receptor And Fluorescein-ghrelmentioning
confidence: 99%
“…The PG is in direct contact with the CSF due to the incomplete ependymal lining in the pineal recess, an extension of the third ventricle [43]. Studies carried out on sheep [29], humans [44] and rodents [45] have confirmed the presence of GHRL in the CSF, through which, it is able to reach most of the forebrain, midbrain and hindbrain areas where GHSR-1a gene expression has been reported. Intracerebroventricular infusions of GHRL into the CSF allows GHRL to influence the PG directly or indirectly through the nerve centers of the brain, such as the mediobasal hypothalamus, that are functionally and anatomically connected with the PG, in which GHSR-1a has been identified [1].…”
Section: Discussionmentioning
confidence: 93%
“…Intracerebroventricular infusions of GHRL into the CSF allows GHRL to influence the PG directly or indirectly through the nerve centers of the brain, such as the mediobasal hypothalamus, that are functionally and anatomically connected with the PG, in which GHSR-1a has been identified [1]. Cabral et al [45] also detected GHRL uptake in the ependymal cells of the ventricular system of the brain, where GHSR-1a is presumably not present. The PG is rich in fenestrated capillaries and canaliculi, through which, even large molecules such as peptides and proteins, including GHRL, can probably penetrate from the CSF into the gland [43].…”
Section: Discussionmentioning
confidence: 99%